2021
DOI: 10.1007/s11482-021-09993-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Household Assets on Child Well-being: Evidence from China

Abstract: This study examined the impact of household assets on multiple dimensions of child well-being using data on 2,583 children aged 10–15 years and their families from the cross-sectional 2016 China Family Panel Studies survey. Household assets were measured as the value of housing assets, cash deposits and household durable goods. Child well-being was measured with 10 indicators in five dimensions: health, education, economic well-being, subjective well-being and family relationships. Multiple linear regression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…Durable goods, in particular, which offer enduring service through repeated usage, play a crucial role [150]. Studies by Adeboju & Oyewole [132], Dutta & Kumar [151], Qi et al [152], and Xiao et al [81] highlighted how these goods elevate household productivity, enable information access, and enhance overall quality of life, elevating the likelihood of escaping poverty. Furthermore, studies by Artha & Dartanto [133], Adeboju & Oyewole [132], and Sevinc [153] suggested that homeownership represents a family's financial stability and is associated with improving their living conditions.…”
Section: Determinants Of Multidimensional Urban Povertymentioning
confidence: 99%
“…Durable goods, in particular, which offer enduring service through repeated usage, play a crucial role [150]. Studies by Adeboju & Oyewole [132], Dutta & Kumar [151], Qi et al [152], and Xiao et al [81] highlighted how these goods elevate household productivity, enable information access, and enhance overall quality of life, elevating the likelihood of escaping poverty. Furthermore, studies by Artha & Dartanto [133], Adeboju & Oyewole [132], and Sevinc [153] suggested that homeownership represents a family's financial stability and is associated with improving their living conditions.…”
Section: Determinants Of Multidimensional Urban Povertymentioning
confidence: 99%
“…In addition, several control variables presenting the characteristics of each cluster are included in the model as suggested by Qi et al (2022), Ajaero et al (2018) and Brooks (2002), including economic regions, areas, ethnicity of household head, household living standards, household size, household head's gender, child's gender, marital status, the mean number of children per household and the mean age of children.…”
Section: Research Modelmentioning
confidence: 99%
“…Additionally, research by Lloyd-Sherlock et al (2012) clarifies the extent to which the child's life satisfaction improves when receiving this assistance. Meanwhile, when analyzing child well-being, studies often look at its correlations with economic indicators, notably household welfare (Qi et al, 2022). For example, Brooks-Gunn (1997) emphasizes the importance of increasing household welfare to reduce common health problems among children such as underweight, asthma, and physical impairment.…”
Section: Introduction *mentioning
confidence: 99%
“…Anak dapat mewarisi kebudayaan dan kegiatan bisnis yang dilakukan keluarga dan sebagai jaminan pada hari tua (Kwiecien and Jedrzychowska 2020;Hasan 2018). Namun hal tersebut menyesuaikan bagaimana suatu keluarga memperlakukan anak mereka (Qi et al 2022).…”
Section: Pendahuluanunclassified